EVALUASI SISTEM REMUNERASI DOSEN BADAN LAYANAN UMUM PERGURUAN TINGGI (Studi Kasus Universitas â€œXâ€) - Agrimahera, Vidia Alif; Adam, Helmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to evaluate lecturer remuneration system in Universityâ€™s Public Service Agency. The Evaluation process is conducted based on the observance of laws and regulations. This research uses qualitative descriptive method. Researcher as the keyÂ instrument. The data obtained through interviews and document collection. The result of the research show that the remuneration system â€œXâ€ University meets the principle of fair, equitable andÂ reasonable. The principle ofÂ proportionality, equality and appropriateness in accordanceÂ to PP Nomor 23 Tahun 2005 and PMK Nomor 10 Tahun 2006. legislation and regulations. But a lack of transparency and a single salary. NeverthelessÂ the principle ofÂ transparency andÂ the singleÂ salary has not been carried out in accordanceÂ withÂ laws and regulations.Â ResearchersÂ proposeÂ model of remuneration in accordance with the regulations. Keywords: remuneration, Public Service Agency, university, lecturer